Implementing an English Fairy Tale YouTube Channel to Enhance 9th Graders' Reading Comprehension - Pande, I Komang Krisna Baba Sanda (Jurnal Penelitian Mahasiswa Indonesia, 2024)
The phenomenon of conventional reading learning is often less interesting for students and results in low engagement in learning activities. This study aims to examine the effectiveness of audio-visual media from the English Fairy Tales YouTube channel in improving students' reading comprehension skills. This study used quantitative method with pre-experimental research design, namely one-group pre-test and post-test. The sample of this study was a group of students selected using simple random sampling technique. Data were collected through reading comprehension tests given before and after treatment with audio-visual media. The test consisted of 30 multiple choice questions which were previously tested for validity and reliability. Data were analyzed using SPSS 25 for Windows, with descriptive and inferential statistical analysis. Descriptive analysis was conducted to determine students' basic reading skills, while inferential analysis used T-test to compare data before and after treatment. The results showed that the use of audio-visual media from the English Fairy Tales YouTube channel significantly improved students' reading comprehension skills. The conclusion of this study is that audio-visual media can be an effective alternative to conventional learning methods in increasing students' interest and engagement in reading activities